Pretransplant, Th17 dominant alloreactivity in highly sensitized kidney transplant candidates - Negi, Sarita; Rutman, Alissa K.; Saw, Chee Loong; Paraskevas, Steven; Tchervenkov, Jean (Frontiers in Transplantation, 2024)
Sensitization to donor human leukocyte antigen (HLA) molecules prior to transplantation is a significant risk factor for delayed access to transplantation and to long-term outcomes. Memory T cells and their cytokines play a pivotal role in shaping immune responses, thereby increasing the risk of allograft rejection among highly sensitized patients. This study aims to elucidate the precise contribution of different CD4+ memory T cell subsets to alloreactivity in highly sensitized (HS) kidney transplant recipients. Stimulation of peripheral blood mononuclear cells (PBMC) with various polyclonal stimulating agents to assess non-specific immune responses revealed that HS patients exhibit elevated immune reactivity even before kidney transplantation, compared to non-sensitized (NS) patients. HS patients’ PBMC displayed higher frequencies of CD4+ T cells expressing IFN, IL4, IL6, IL17A, and TNF and secreted relatively higher levels of IL17A and IL21 upon stimulation with PMA/ionomycin. Additionally, PBMC from HS patients stimulated with T cell stimulating agent phytohemagglutinin (PHA) exhibited elevated expression levels of IFN, IL4 and, IL21. On the other hand, stimulation with a combination of resiquimod (R848) and IL2 for the activation of memory B cells demonstrated higher expression of IL17A, TNF and IL21, as determined by quantitative real-time PCR.